ROLE BAITUL MAAL WAT TAMWIL (BMT) IN BOARDING SCHOOL SIDOGIRI EMPOWERMENT AS ALTERNATIVE SMALL AND MEDIUM (MSMES) - Al Mustofa, Mohammad Imsin (Entrepreneur, 2011)
AbstractBaitul maal wattamwil (BMT) is a microfinance institution that uses the approach of Islamic patterns. The existence of BMT MMU in the midst of Muslim society / the students and the PondokPesantren Sidogiri is such an empowerment model of small and medium businesses which has been running since 17 July 1997. BMT MMU Sidogiri stands and operates based on the spirit of dedication and sense of community is concerned about the economic existence around the boarding school are entwined by the practice of money lenders, who became the attention and concern of the owner Boarding Schools and finally stood MMU SidogiriBMT. From this background emerged a few questions What is the role of Baitul Maal wattamwil (BMT) Sidogiri At boarding school in empowering small and medium enterprises (SMEs)?. the purpose of this study was to determine and analyze the role of Baitul Maalwattamwil (BMT) At boarding school in empowering business Sidogiri small-medium enterprises (MSMEs). BMT-MMU Sidogiri role in enhancing the empowerment of small and medium business is a real happening, and is one of the microfinance institution with a proper system of sharia to be made in alternative models to be developed in increasing empowerment of small and medium enterprises in the future. This can be seen from some indications that the number of member development, asset and his work, microfinance institutions such as BMT MMU Sidogiri.Keywords: baitul maal wattamwil (BMT), UMKM AbstrakBaitul maal wattamwil (BMT) merupakan lembaga keuangan mikro yang menggunakan pendekatan pola Islam. Keberadaan BMT MMU di tengah-tengah masyarakat muslim / mahasiswa dan Sidogiri PondokPesantren adalah sebuah model pemberdayaan usaha kecil dan menengah yang sudah berjalan sejak 17 Juli 1997. BMT MMU Sidogiri berdiri dan beroperasi berdasarkan semangat dedikasi dan rasa komunitas yang bersangkutan tentang keberadaan ekonomi di seluruh pondok pesantren yang terjalin oleh praktek rentenir, yang menjadi perhatian dan keprihatinan dari Sekolah pemilik Boarding dan akhirnya berdiri MMU SidogiriBMT. Dari latar belakang ini muncul beberapa pertanyaan Apa peran Baitul Maal wattamwil (BMT) Sidogiri Di sekolah asrama dalam memberdayakan usaha kecil dan menengah (UKM)?. tujuan penelitian ini adalah untuk mengetahui dan menganalisis peran Baitul Maalwattamwil (BMT) Di sekolah asrama dalam memberdayakan usaha Sidogiri kecil menengah (UMKM). BMT-MMU Sidogiri peran dalam meningkatkan pemberdayaan usaha kecil dan menengah adalah peristiwa nyata, dan merupakan salah satu lembaga keuangan mikro dengan sistem syariah yang tepat harus dibuat dalam model-model alternatif untuk dikembangkan dalam meningkatkan pemberdayaan usaha kecil dan menengah di masa depan. Hal ini terlihat dari beberapa indikasi bahwa jumlah pengembangan anggota, aset dan karyanya, lembaga keuangan mikro seperti BMT MMU Sidogiri.Kata kunci: baitul maal wattamwil (BMT), UMKM